2005
DOI: 10.1007/s11746-005-1048-7
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol composition of oil from Pistacia atlantica fruit growing in Algeria

Abstract: The distribution of FA between the sn-2 and sn-1,3 positions of TAG from Pistacia atlantica fruit oil of Algeria has been determined. Unsaturated FA showed a preference for the internal position. Linoleic and oleic acids occurred predominantly in the sn-2 position with lesser amounts evenly distributed between the sn-1 and sn-3 positions, as generally found in vegetable oils. The oil was found to contain TAG that were trisaturated (0.93%), disaturated (15.06%), monosaturated (44.64%), and triunsaturated (38.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
2
9
0
1
Order By: Relevance
“…Eight of them are the majority (Table 1), and in order of decreasing abundance are: PLO [186.05 mg g −1 of total lipid (TL)], POO (158.25 mg g −1 TL), OLO (102.57 mg g −1 TL), OOO (95.83 mg g −1 TL), PLL (93.78 mg g −1 TL), PLP (67.43 mg g −1 TL), LLO (65.40 mg g −1 TL) and POP (60.20 mg g −1 TL), where P represents palmitic acid; L, linoleic acid; and O, oleic acid. A determination of the TAG composition of Pistacia atlantica fruit, a related species belonging to the Anacardiaceae family, shows the prevalence of PLO (8%) and POO (15%), 13 which is consistent with our results. In contrast, the occurrence of TAG molecular species in some vegetable oils showed that in almond, olive and Pinus pinea, the major species are, respectively, LLL, OOO and LLO.…”
Section: Resultssupporting
confidence: 91%
“…Eight of them are the majority (Table 1), and in order of decreasing abundance are: PLO [186.05 mg g −1 of total lipid (TL)], POO (158.25 mg g −1 TL), OLO (102.57 mg g −1 TL), OOO (95.83 mg g −1 TL), PLL (93.78 mg g −1 TL), PLP (67.43 mg g −1 TL), LLO (65.40 mg g −1 TL) and POP (60.20 mg g −1 TL), where P represents palmitic acid; L, linoleic acid; and O, oleic acid. A determination of the TAG composition of Pistacia atlantica fruit, a related species belonging to the Anacardiaceae family, shows the prevalence of PLO (8%) and POO (15%), 13 which is consistent with our results. In contrast, the occurrence of TAG molecular species in some vegetable oils showed that in almond, olive and Pinus pinea, the major species are, respectively, LLL, OOO and LLO.…”
Section: Resultssupporting
confidence: 91%
“…7b, Table 1). Previous studies on the composition of oils derived from the Pistacia atlantica fruits utilizing HPLC did not report the presence of syringic acid (Yousfi et al, 2005). The use of alkaline fusion in this work undoubtedly led to the recovery of this compound, not identified by other techniques.…”
Section: High Performance Liquid Chromatography-tandem Mass Spectromementioning
confidence: 70%
“…Chemical studies on Bene mainly regarded the fatty acids and triglycerides (Benhassaini, Bendahmane, & Benchalgo, 2007;Farhoosh et al, 2008;Yousfi, Nadjemi, Belal, Bombarda, & Gaydou, 2005), chemical composition of oleoresin and essential oils (Benhassaini, Bendeddouche, Mehdadi, & Romane, 2008;Mercherara-Idjeri, Hassani, Castola, & Casanova, 2008;Tzakou, Bazos, & Yannitsaros, 2007) and flavonoids (Kawashty, Mosharrafa, EL-Gibali, & Saleh, 2000;Pietta, 2000). However, there have been few studies on phenolic compounds in Bene, which are potent antioxidants and free radical scavengers (Farhoosh, Tavassoli-Kafrani, & Sharif, 2011;Gourine et al, 2010).…”
Section: Introductionmentioning
confidence: 99%